Plant growth, salt removal capacity, and forage nutritive value of the annual euhalophyte Suaeda salsa irrigated with saline water - Wang, Ning; Zhao, Zhenyong; Zhang, Xinyi; Liu, Sihai; Zhang, Ke; Hu, Mingfang (Frontiers in Plant Science, 2023)
Sustainable agricultural development in semi-arid and arid regions is severely restricted by soil and water salinization. The representative halophyte Suaeda salsa, which can be irrigated with saline water and cultivated on saline soils, is considered to be a potential solution to freshwater scarcity, soil salinization, and fodder shortage. However, the salt-removal capacity and differences in the forage nutritive value of S. salsa under different saline-water treatments remain unknown. By methods of field trials and randomized blocks design, we quantified the salt accumulation in the aboveground biomass, and the biochemical and nutritive value of field-cultivated S. salsa in arid northwestern China under irrigation with water of different salinities (freshwater, 10, 20, 30, 40 g/L NaCl). The fresh and dry weights of S. salsa increased first, then decreased, with increase in salinity. The salt content of the aboveground biomass increased to a constant range and thus the salt extraction of S. salsa was relatively stable under different salinities of irrigation water. Under the experimental conditions, the crude protein content significantly increased to 9.45 % dry weight (DW) first and then decreased to 6.85 % DW with increase in salinity (p < 0.05). The neutral detergent fiber (42.93 %-50.00 % DW) and acid detergent fiber (34.76 %-39.70 % DW) contents were suitable for forage. The contents of trace elements, such as copper and zinc, were significantly promoted by irrigation with saline water (p < 0.05). Suaeda salsa forage is of high nutritive value for livestock and contains a low concentration of anti-nutrients. Thus, S. salsa can be considered for cultivation in saline soils irrigated with saline water and provides a viable additional source of fodder in arid regions where the availability of freshwater and non-saline arable land is limited.